2012
DOI: 10.1074/jbc.m111.338921
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among Positions in the Third and Fourth Membrane-associated Domains at the Intersubunit Interface of the N-Methyl-d-aspartate Receptor Forming Sites of Alcohol Action

Abstract: Background:The NMDA receptor is a major target of alcohol action in the brain. Results: Four pairs of residues at the M3-M4 domain intersubunit interfaces interact to regulate gating and alcohol sensitivity. Conclusion: NMDA receptors contain putative sites of alcohol action at the M3-M4 domain interfaces. Significance: Identifying molecular sites of alcohol action on its targets is essential for understanding its actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 55 publications
6
78
3
Order By: Relevance
“…Positive correlations between substituent side chain volume and ethanol sensitivity are consistent with a model in which ethanol acts by occupying a critical volume, as has been shown in other alcohol-sensitive ligand-gated ion channels Ye et al, 1998;Koltchine et al, 1999;Yamakura et al, 1999;Kash et al, 2003). The lack of such a correlation in our study may indicate that the side chain at 636 does not project into the interior of an alcohol binding site but rather forms part of the outer boundary of such a site (Ren et al, 2012). In this case, the side chain at 636 would regulate receptor function in a more complex manner depending on its interactions with other side chains in its environment.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Positive correlations between substituent side chain volume and ethanol sensitivity are consistent with a model in which ethanol acts by occupying a critical volume, as has been shown in other alcohol-sensitive ligand-gated ion channels Ye et al, 1998;Koltchine et al, 1999;Yamakura et al, 1999;Kash et al, 2003). The lack of such a correlation in our study may indicate that the side chain at 636 does not project into the interior of an alcohol binding site but rather forms part of the outer boundary of such a site (Ren et al, 2012). In this case, the side chain at 636 would regulate receptor function in a more complex manner depending on its interactions with other side chains in its environment.…”
Section: Discussionsupporting
confidence: 90%
“…In that study, we identified five positions in the GluN1 and GluN2A subunits that had not been previously shown to regulate ethanol sensitivity. Substitution mutations at a few of these individual positions, such as GluN2A(L824), had no effect on ethanol sensitivity by themselves (Honse et al, 2004) but influenced ethanol action only in concert with mutations at their paired position (Ren et al, 2012). In contrast, we found that tryptophan substitution at F636 in the M3 domain of GluN2A (Fig.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations